TRANSFORMING MATHEMATICS LEARNING: IMPROVING STUDENT MOTIVATION BY INTEGRATING PROJECT-BASED LEARNING AND SIMULATION - Radhya Yusri; Anuar Mohd Yusof; Azlin Sharina, (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2024)
The a lack of study that examines the combination of these two methods in learning Geometry, especially in terms of its effect on student learning motivation, this study is here to answer this need. The purpose of this study is to determine the extent to which the integration of project-based learning and simulation can increase student learning motivation. This study is a quantitative research with A group pre-test and post-test design. This study involved thirty students of Universitas PGRI Sumatera Barat, Indonesia. Data collection was done through questionnaire. Data analysis was conducted with One-way ANOVA. The results showed that students who studied using the integration of project-based learning and simulation had a significant level of learning motivation. Students felt more engaged and academically challenged, which contributed to their increased motivation. This study concludes that the integration of project-based learning and simulation in mathematics learning is effective in increasing students' learning motivation. The findings provide practical implications for educators in designing more innovative and effective learning strategies to improve the quality of mathematics education at the tertiary level. Further research is recommended to explore the impact of the integration of this learning model on other skills and examine its applicability in other disciplines.